Effects of the Variation of SUSY Breaking Scale on Yukawa and Gauge Couplings Unification - Konsam Sashikanta Singh; N. Nimai Singh (Advances in High Energy Physics)
The present analysis addresses an interesting primary question on how do the gauge and Yukawa couplings unification scales vary with varying SUSY breaking scales ms, assuming a single scale for all supersymmetric particles. It is observed that the gauge coupling unification scale increases with ms whereas third-generation Yukawa couplings unification scale decreases with ms. The rising of the unification scale and also the mass of the color triplet multiplets is necessary to increase the proton decay lifetime; the analysis is carried out with two-loop RGEs for the gauge and Yukawa couplings within the minimal supersymmetric SU(5) model, while ignoring for simplicity the threshold effects of the heavy particles, which could be as large as a few percentages.